2018
DOI: 10.12688/f1000research.15162.1
|View full text |Cite
|
Sign up to set email alerts
|

How to incorporate patient and public perspectives into the design and conduct of research

Abstract: International government guidance recommends patient and public involvement (PPI) to improve the relevance and quality of research.  PPI is defined as research being carried out ‘with’ or ‘by’ patients and members of the public rather than ‘to’, ‘about’ or ‘for’ them ( http://www.invo.org.uk/). Patient involvement is different from collecting data from patients as participants.  Ethical considerations also differ.  PPI is about patients actively contributing through discussion to decisions about research desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
132
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(151 citation statements)
references
References 44 publications
(50 reference statements)
0
132
0
2
Order By: Relevance
“…The level of reporting of involvement of stakeholders in systematic reviews, and the inconsistencies in which this is reported, must be improved so that guidance around how people can be involved in systematic reviews can be developed and the impact of involvement explored. This scoping review lends support to calls for high-quality training materials and examples of best practice to support active patient and public involvement and enhance the relevance, usefulness and accessibility of systematic reviews [ 2 , 16 , 18 , 61 , 63 ]. We identified a subset of 30 papers which we judged to provide a comprehensive description of stakeholder involvement in systematic reviews, and used these examples to summarise different ways in which stakeholders have been involved in systematic reviews.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The level of reporting of involvement of stakeholders in systematic reviews, and the inconsistencies in which this is reported, must be improved so that guidance around how people can be involved in systematic reviews can be developed and the impact of involvement explored. This scoping review lends support to calls for high-quality training materials and examples of best practice to support active patient and public involvement and enhance the relevance, usefulness and accessibility of systematic reviews [ 2 , 16 , 18 , 61 , 63 ]. We identified a subset of 30 papers which we judged to provide a comprehensive description of stakeholder involvement in systematic reviews, and used these examples to summarise different ways in which stakeholders have been involved in systematic reviews.…”
Section: Discussionmentioning
confidence: 84%
“… Email and phone communication throughout the review. No information provided No information provided Coon et al [ 63 ] An Expert Advisory group—involved throughout the project, including commenting on the protocol, editing draft chapters and responding to ad hoc questions. In addition, a series of four events were held: Event 1 aimed to share information and explore experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Engagement is considered multi-directional, resulting in "informed decisionmaking about the selection, conduct, and use of the research" [32]. Depending on the context, engagement may also be termed collaboration, involvement, or partnership [36]. Herein, we will use the term "stakeholder engagement."…”
Section: Engagementmentioning
confidence: 99%
“…A recurring theme from researchers is a lack of peer‐to‐peer learning in this space. Even when a researcher may understand the concept of PPI, its implementation—even with the vast array of available ‘toolkits’—can be challenging …”
Section: Introductionmentioning
confidence: 99%